Human Obesity and Type 2 Diabetes Are Associated With Alterations in SREBP1 Isoform Expression That Are Reproduced Ex Vivo by Tumor Necrosis Factor-α - Sewter, Ciaran; Berger, Dirk; Considine, Robert V.; Medina, Gema; Rochford, Justin; Ciaraldi, Theodore; Henry, Robert; Dohm, Lynis; Flier, Jeffrey S.; O’Rahilly, Stephen; Vidal-Puig, Antonio J. (Diabetes (New York, N.Y.), 2002)
Human Obesity and Type 2 Diabetes Are Associated With Alterations in SREBP1 Isoform Expression That Are Reproduced Ex Vivo by Tumor Necrosis Factor-α Ciaran Sewter 1 , Dirk Berger 1 , Robert V. Considine 2 , Gema Medina 1 3 , Justin Rochford 1 , Theodore Ciaraldi 4 , Robert Henry 4 , Lynis Dohm 5 , Jeffrey S. Flier 6 , Stephen O’Rahilly 1 and Antonio J. Vidal-Puig 1 1 Departments of Clinical Biochemistry and Medicine, University of Cambridge, Addenbrooke’s Hospital, Cambridge, U.K. 2 Department of Medicine, Indiana University School of Medicine, Indianapolis, Indiana 3 Instituto de Investigaciones Biomedicas “Alberto Sols” CSIC, Universidad Autonoma de Madrid, Madrid, Spain 4 VA San Diego Health Care System and Department of Medicine, University of California, San Diego, La Jolla, California 5 Department of Biochemistry, School of Medicine, East Carolina University, Greenville, North Carolina 6 Department of Medicine, Beth Israel Deaconess Medical Center, Harvard Medical School, Boston, Massachusetts Abstract Sterol regulatory element binding protein (SREBP)-1 is a transcription factor with important roles in the control of fatty acid metabolism and adipogenesis. Little information is available regarding the expression of this molecule in human health or disease. Exposure of isolated human adipocytes to insulin enhanced SREBP1 gene expression and promoted its proteolytic cleavage to the active form. Furthermore, 3 h of in vivo hyperinsulinemia also significantly increased SREBP1 gene expression in human skeletal muscle. Transcript levels of SREBP1c, the most abundant isoform in adipose tissue, were significantly decreased in the subcutaneous adipose tissue of obese normoglycemic and type 2 diabetic subjects compared with that of nonobese normoglycemic control subjects. In skeletal muscle, SREBP1 expression was significantly reduced in type 2 diabetic subjects but not in obese subjects. Within the diabetic group, the extent of SREBP1 suppression was inversely related to metabolic control and was normalized by 3 h of in vivo hyperinsulinemia. Exposure of isolated human adipocytes to tumor necrosis factor-α (TNF-α) produced a marked and specific decrease in the mRNA encoding the SREBP1c isoform and completely blocked the insulin-induced cleavage of SREBP1 protein. Thus, both the expression and proteolytic maturation of human SREBP1 are positively modulated by insulin. The specific reduction in the SREBP1c isoform seen in the adipose tissue of obese and type 2 diabetic subjects can be recapitulated ex vivo by TNF-α, suggesting a possible mechanism for this association. Footnotes Address correspondence and reprint requests to Antonio J. Vidal-Puig, MD, PhD, University of Cambridge, Departments of Clinical Biochemistry and Medicine, Box 232, Addenbrooke’s Hospital, Hills Road, Cambridge, CB2 2QR, U.K. E-mail: ajv22atcam.ac.uk . Received for publication 27 June 2001 and accepted in revised form 27 December 2001. C.S. and D.B. contributed equally to this study. ADD1, adipocyte determination differentiation factor 1; AH, Addenbrooke’s Hospital; bHLH, basic helix loop helix leucine zipper; DMEM, Dulbecco’s modified Eagle’s medium; ECL, enhanced chemiluminescence; ECU, East Carolina University; FBS, fetal bovine serum; IU, Indiana University; PPARγ, peroxisome proliferator–activated receptor-γ; SCAP, sterol regulatory element binding protein-cleavage–activating protein; SREBP; sterol regulatory element binding protein; UCSD, University of California San Diego. DIABETES